2022
DOI: 10.12968/jowc.2022.31.7.548
|View full text |Cite
|
Sign up to set email alerts
|

When time does not heal all wounds—the use of medical grade honey in wound healing: a case series

Abstract: Objective: Hard-to-heal wounds can be caused by persistent infections or an excess of inflammatory cytokines, proteases and oxidants, and can severely impact the quality of life (QoL) of patients. Due to the paucity of effective treatments and increased resistance to antibiotics, new and improved therapies are required to resolve infections and to simultaneously enhance the healing trajectory. Medical grade honey (MGH) may be a novel and effective treatment approach. Methods: In this case series, we have descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Previous treatments with different antiseptic or antibiotic products were without adequate response. Local clinical signs of infection gradually decreased and completely resolved within a time range from 1–4 weeks, in concordance with other studies [ 30 , 31 , 32 ]. In this study, wound swabs and microbial culturing were not taken and performed since the diagnosis was made by clinical assessment of different signs of local infection, such as necrosis, pain, malodor, erythema, warmth, edema, exudate, and delayed healing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous treatments with different antiseptic or antibiotic products were without adequate response. Local clinical signs of infection gradually decreased and completely resolved within a time range from 1–4 weeks, in concordance with other studies [ 30 , 31 , 32 ]. In this study, wound swabs and microbial culturing were not taken and performed since the diagnosis was made by clinical assessment of different signs of local infection, such as necrosis, pain, malodor, erythema, warmth, edema, exudate, and delayed healing.…”
Section: Discussionsupporting
confidence: 92%
“…We did not observe any adverse effects, and with the quick recession of local signs of infection and the positive healing response, the wound-dressing changes were extended, reducing in this way the total cost of the therapeutic protocol. Several studies proved the broad-spectrum antimicrobial activity of MGH against common wound microorganisms, including Staphylococcus aureus (including methicillin-resistant Staphylococcus aureus, MRSA ), Pseudomonas aeruginosa , and Escherichia coli , even in cases where antibiotics were ineffective [ 18 , 30 , 31 , 32 , 33 , 34 ]. Recent reviews provide an extensive list of microorganisms with susceptibility to the antimicrobial activity of MGH [ 19 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The broad-spectrum antimicrobial activity of MGH makes it effective in preventing infections, while also promoting wound healing. Previous studies have demonstrated that MGH is effective in resolving infections in several types of wounds caused by different types of bacteria, and can even eradicate biofilms [20,30,31,54]. The supplements in the MGH formulation L-Mesitran further enhance these beneficial properties [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…The honey used in L-Mesitran can be of different floral and geographical origin but always complies with strict MGH criteria to guarantee safety, quality, and efficacy [22]. Hence, MGH is free of pesticides, herbicides, heavy metals, antibiotics, and endospores/micro-organisms (due to gamma irradiation) and adheres to certain physicochemical characteristics [30]. The other ingredients enhance the antimicrobial activity and improve the applicability [54][55][56].…”
Section: Treatment Protocol and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation